Effect of Return on Equity and Debt to Equity Ratio to Stock Return - Iman Lubis; Farida Nur Alfiyah (YPPP AL-AMSI, 2021)
This study aims to see the effect of the effect of Return on Equity (ROE) and Debt to Equity Ratio (DER) on Stock Return. Research type in quantitative research. The research method used is the multiple linear regression method, with the variable X_1 Return On Equity (ROE), the variable X_2 Debt To Equity Ratio and the variable Y Stock Return. Collecting data in this study using descriptive analysis techniques. The documents used are financial reports from 2009 to 2018 which are listed on the Indonesia Stock Exchange. The results of the partial test research (t test) show that there is a positive and significant influence between the Return on Equity (ROE) of Stock Return, it can be seen from the value of t count 2.598> t table 2.365, with a significance value of 0.044 <0.05 can be obtained from Ho1 rejected and Ha1 accepted. Then the results of the Partial Test (t test) show that there is a negative and insignificant influence between the Debt To Equity Ratio (DER) on Stock Returns, it can be seen from the value of tcount -0.228 > ttabel -2.365, with a significance value of 0.825> 0.05 then it can be obtained that Ho2 is accepted and Ha2 is rejected. Furthermore, the results of the research simultaneously (Test f) show that there is no significant influence between Return On Equity (ROE) and Debt To Equity Ratio (DER) on Stock Return, it can be seen from the value of the value of 3.060 <ftabel 4.46 with a significance value. 0.111. Because the significant value is greater than 0.111> 0.05, it can be concluded that Ho3 is accepted and Ha3 is rejected.